Fabrication of GaN vertical junction barrier Schottky diode by Mg diffusion from shallow N/Mg ion-implantation segment - Woong Kwon; Yuta Itoh; Atsushi Tanaka; Hirotaka Watanabe; Yoshio Honda; Hiroshi Amano (Applied Physics Express)
A vertical GaN p–n junction diode (PND) and junction barrier Schottky diode (JBSD) were fabricated by selective Mg diffusion. Mg was diffused from a shallow N/Mg ion-implantation segment to a depth of 800 nm with a concentration of 1 × 10 ^17 –3 × 10 ^18 cm ^−3 by annealing with an AlN capping layer at 1300 ℃ for 5 min under atmospheric N _2 pressure. The PND and JBSD exhibited specific on-resistances of 2.3–2.6 mΩ cm ^2 and repeatable breakdowns at 1.95 kV without degradation in breakdown voltage or leakage current. Additionally, the JBSD achieved a high-on/off ratio of 9.1 × 10 ^7 between 1.5 V and −1 kV.